2013
DOI: 10.1155/2013/156459
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Catamenial Dermatoses

Abstract: Circulating sex hormones follow major fluctuations during the ovarian cycle. The so-called premenstrual syndrome represents a global condition grouping the diversity of catamenial disorders. At the skin level, the sebaceous gland activity is obviously modulated by these endocrine fluctuations. In addition, a series of pathological manifestations take place simultaneously in some women. Among them, the most frequent skin condition is represented by catamenial acne. Concurrently, the autoimmune progesterone derm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Nguyen et al reported that 45% of cases had a history of exogenous exposure in their review of 89 cases. Autoimmunity is favored as many of these patients experience a flare with exposure to progesterone and cessation of symptoms with removal of progesterone . In addition, antibodies to progesterone have been showed in some patients …”
Section: Discussionmentioning
confidence: 99%
“…Nguyen et al reported that 45% of cases had a history of exogenous exposure in their review of 89 cases. Autoimmunity is favored as many of these patients experience a flare with exposure to progesterone and cessation of symptoms with removal of progesterone . In addition, antibodies to progesterone have been showed in some patients …”
Section: Discussionmentioning
confidence: 99%
“…Circulating sex hormones (i.e ., estrogens, progesterone, and androgens) regulate skin homeostasis. Thus, cutaneous disease may be influenced by the menstrual cycle, specifically by hormonal modulation of skin cell activity (Hermanns-Le et al, 2013). The menstrual cycle is split into two phases: the follicular phase (dominated by estradiol) and the luteal phase (dominated by progesterone).…”
Section: Introductionmentioning
confidence: 99%
“…Estrogen is also involved in the regulation of ultraviolet (UV)-induced skin damage and pigmentation by inducing intraepidermal melanogenesis, which causes transient patchy hyperpigmentation around the eyelids prior to menstruation. The effect of progesterone on skin physiology is not well known (Farage et al, 2009, Hermanns-Le et al 2013, Stephens, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Autoimmune progesterone dermatitis (APD) is a rare skin condition with a varying morphology, appearing on a monthly basis during the luteal phase of the menstrual cycle. Progesterone levels gradually rise after ovulation, reaching a peak concentration about 7 days before menstruation, then decreasing 1 to 2 days after menses, when there is a spontaneous resolution of APD …”
Section: Introductionmentioning
confidence: 99%
“…Sex hormones modulate the immune and inflammatory functions of cells, including mast cell degranulation . Several studies point to an autoimmune mechanism mediated by Th1 lymphocytes targeting endogenous progesterone, as in delayed hypersensitivity reactions . In women undergoing exogenous progesterone prior to APD diagnosis, Th2 cells and immunoglobulin IgE may also play a role…”
Section: Introductionmentioning
confidence: 99%